Vasily Nikolaevich Khitrovo: Peculiarities of Service in the Naval Ministry in 1856-1863 under the Command of Grand Duke Konstantin Nikolaevich - Galina V. Aksenova (RUDN Journal of Russian History)
The author considers the life V.N. Khitrovo (1834-1903) who was to a greater extent known as the founder of the Orthodox Palestine Society and, to a lesser extent, as a statesman. In 1856, he became an official in the Naval Ministry, where he served under the command of Grand Duke Konstantin Nikolayevich until April 1863, during the transformation of the financial reporting system in the Naval Ministry. The article describes for the first time V.N. Khitrovo’s service in the Office of the Control Department and the Commissariat Department of the Ministry and shows the features of his service. The author reveals the significance of V.N. Khitrovo's business trip to France in 1858. The introduction into scientific use of the documents from the naval archive made it possible to characterize the nature of Khitrovo’s activity during the studies and the practical training he had in the Reporting Department of the French Ministry of Finance and Arsenal. In addition, the author analyzed for the first time V.N. Khitrovo’s works devoted to the history of accounting and justification of the need to introduce a double-entry bookkeeping system. The conducted research allowed us to come to the conclusion that during his years of service in the Naval Ministry, V.N. Khitrovo gained critical experience in organizing financial control and accounting, which later allowed him to effectively organize the financial activities of the Imperial Orthodox Palestine Society.